International Structural Competitiveness and the Hierarchy in the World Economy: Theoretical and Empirical Research Evidence. (17th February 2022) - Markaki, Maria; Economakis, George
Abstract : The aim of this paper is to determine the level of competitiveness of national economies and their resulting hierarchy in the world economy. Based on the assumption that there is a structural relationship between the competitiveness of a national economy and the level of its economic development, we identify the main structural factors of international competitiveness. These factors are the degree of diversification of the productive structure of a national economy and the strength of its domestic sectoral productive linkages—which are both related to the level of industrial and technological development and the technological structure of exports. The Technologically Advanced Domestic Value Added in Exports, which condenses the above structural factors, is proposed as a measure of the level of competitiveness of national economies. This measure is implemented in order to determine the hierarchical position of 43 economies in terms of their international competitiveness. In addition, another measure of international competitiveness, the Economic Complexity Index, is examined and tested. When comparing the examined economies' hierarchical positions obtained by using the two measures, a high correlation and a strong positive linear relationship between them is revealed.